Analisis Puisi “Penglihatan” Karya Adimas Immanuel Menggunakan Pendekatan Ekspresif - Desi Natalia Sihombing; Jihan Aufa Nadira; Ika Febriana (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
Poetry is part of a literary work that has aesthetic value and is visualized in verses with full meaning. The purpose of this study is to analyze poetry with an expressive approach. The method used in this research is descriptive method with content analysis, by analyzing poetry with an expressive approach. Expressive is an approach in a very scientific and well-studied way. Because the expressive approach to poetry is based on our interpretation of a structured poem. So, previously poetry could not be understood by everyone who did not understand the world of literature because the words contained figures of speech (hyperbole in particular) became understandable to everyone who did not know about the world of literature because the words in the poem were interpreted in ordinary words. What used to contain a lot of figurative language became words that are common or easily understood by everyone.